Rút gọn phân thức
\(\frac{xy^3-x^2y}{x^2+xy}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{x^2+3xy+2y^2}{x^3+2x^2y-xy^2-2y^3}\)
\(=\dfrac{\left(x+y\right)\left(x+2y\right)}{x\left(x^2-y^2\right)+2y\left(x^2-y^2\right)}\)
\(=\dfrac{x+y}{x^2-y^2}\)
\(=\dfrac{1}{x-y}\)
\(\frac{x^3-x^2y-xy^2+y^3}{x^3+x^2y-xy^2-y^3}=\frac{\left(x^3-xy^2\right)-\left(x^2.y-y^3\right)}{\left(x^3-xy^2\right)+\left(x^2y-y^3\right)}=\frac{x.\left(x^2-y^2\right)-y.\left(x^2-y^2\right)}{x.\left(x^2-y^2\right)+y.\left(x^2-y^2\right)}=\frac{\left(x-y\right)\left(x^2-y^2\right)}{\left(x+y\right)\left(x^2-y^2\right)}=\frac{x-y}{x+y}\)
\(\frac{\left(x-1\right)^3}{x^2y-xy-x+1}=\frac{\left(x-1\right)^3}{xy\left(x-1\right)-\left(x-1\right)}=\frac{\left(x-1\right)^3}{\left(xy-1\right)\left(x-1\right)}=\frac{\left(x-1\right)^2}{xy-1}=\frac{x^2-2x+1}{xy-1}\)
\(\frac{xy^3-x^2y}{x^2+xy}=\frac{xy\left(y^2-x\right)}{x\left(x+y\right)}=\frac{y\left(y^2-x\right)}{x+y}=\frac{y^3-xy}{x+y}\)